Factors Affecting Village Financial Management Accountability - Opik Taufik; Syafrizal Ikram (Universitas Padjadjaran, 2022)
This study aims to analyze the effect of human resource competence and organizational commitment on the use of information technology and its impact on village financial management accountability. This study uses a quantitative approach. The population in this study are villages in Tasikmalaya Regency. This study used the proportional sampling method with a total sample of 187 respondents. The sample of this study consisted of village heads, village secretaries, heads of administrative and general affairs, heads of government sections, and heads of financial affairs from 187 villages in Tasikmalaya Regency. The data collection method is distributing questionnaires measured by a Likert scale. Data analysis was carried out using path analysis techniques. The results of the study indicate that the competence of human resources and organizational commitment affect the utilization of information technology; human resource competence; organizational commitment; and the use of information technology affect the accountability of village financial management. The results of the path analysis show that the use of information technology is proven to mediate the human resource competence and organizational commitment to the accountability of village financial management.